Penerapan Pembelajaran Berbasis Masalah Terhadap Berpikir Kritis Siswa SD Kelas V pada Materi Daur Air - Naomi, Bezella; Gusrayani, Diah; Sujana, Atep (Jurnal Pena Ilmiah, 2019)
This study aims to determine the application of problem-based learning to critical thinking of Class V elementary school students on water cycle material. The population of this study was the fifth grade students of the Public Elementary School in Sedong Subdistrict, Cirebon Regency with a total of 21 schools with the research sample of SDN 1 Panongan and SDN 1 Panongan Lor in class V because the design used was quasi-experimental. Based on the results of the study concluded that problem-based learning can improve students' critical thinking on water cycle material significantly; Conventional learning in water cycle material can significantly improve students' critical thinking; and There is a difference in the improvement of students' critical thinking skills in a significant water cycle material between problem-based learning and conventional learning, which occurs because problem-based learning is significantly better with an average gain of 0.323 compared to conventional learning with an average gain of 0.176. Therefore problem-based learning is better than conventional learning.